Concrete curing agent and preparation method and performance testing method thereof
By combining components such as lithium silicate, magnesium fluorosilicate, nano silica, etc. with surfactants and additives, an efficient and environmentally friendly concrete curing agent is prepared, which solves the unstable concrete performance in the prior art and The problem of environmental pollution has significantly improved the strength, wear resistance and durability of concrete, and is suitable for large-scale production.
Patent Information
- Application Number
- CN202411335567.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing concrete curing agents have poor results in improving concrete performance, unstable performance and great environmental pollution, making it difficult to meet the construction industry's demand for efficient, environmentally friendly and stable performance.
The concrete curing agent is prepared by mixing evenly by mixing the strength, hardness, wear resistance and durability of the concrete, and the strength, hardness, wear resistance and durability of the concrete are improved, and Verify its effectiveness through performance testing methods.
It significantly improves the compressive strength, wear resistance, seepage resistance and durability of concrete, reduces environmental pollution, is suitable for large-scale production, and meets the early strength needs of engineering construction.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of the construction industry, and in particular to a concrete curing agent and a preparation method and a performance testing method thereof. Background Art
[0002] With the continuous development of the construction industry, the performance requirements for concrete are getting higher and higher. During the use of concrete, due to the influence of the external environment, such as moisture, chemicals, wear, etc., it is easy to have problems such as reduced strength, surface sanding, cracking, etc., which will affect the service life and safety of concrete. In order to solve these problems, people usually use concrete curing agents to improve the performance of concrete.
[0003] At present, there are many types of concrete curing agents on the market, but they generally have problems such as unsatisfactory curing effect, unstable performance, and environmental pollution. Therefore, it is of great practical significance to develop an efficient, environmentally friendly, and stable concrete curing agent. Summary of the invention
[0004] Based on the above problems, the purpose of the present invention is to provide a concrete curing agent and a preparation method and a performance testing method thereof, wherein the curing agent can effectively improve the strength, hardness, wear resistance and durability of concrete, and has good environmental performance. The method is simple, easy to operate, low-cost and suitable for large-scale production.
[0005] In response to the above problems, the following technical solutions are provided: a concrete curing agent, comprising the following components in parts by weight: 18-22 parts of lithium silicate, 10-13 parts of magnesium fluorosilicate, 7-10 parts of nano-silicon dioxide, 2.5-3.5 parts of surfactant, 3-8 parts of additive, and the balance is water.
[0006] Among the above components, lithium silicate adopts a high-purity industrial-grade product, which can react with calcium hydroxide in concrete to generate calcium silicate hydrate, thereby enhancing the strength and hardness of concrete, and improving the wear resistance and durability of concrete. Magnesium fluorosilicate is a white crystalline powder with good chemical stability. It can promote the rapid hardening of concrete in concrete curing agent, improve the early strength of concrete, and also enhance the impermeability and chemical corrosion resistance of concrete. Nano silicon dioxide particles are fine, have a large specific surface area and activity, can fill the tiny pores in concrete, make concrete more compact, thereby improving the strength, impermeability and durability of concrete. The surfactant is a non-ionic surfactant. The non-ionic surfactant is specifically fatty alcohol polyoxyethylene ether. This surfactant can reduce the surface tension of concrete curing agent, so that it can better penetrate into the interior of concrete, and improve the bonding force between curing agent and concrete. Water is used as a solvent to fully mix the components to form a uniform and stable solution. Deionized water or purified water is used to avoid the adverse effects of impurities in the water on the performance of concrete curing agent.
[0007] The present invention further adopts that the auxiliary agent is one or a combination of a penetrant, a defoamer or an early strength agent. The penetrant is polyethylene oxide or an organosiloxane polycondensate. The defoamer is an organosilicon defoamer, accounting for 1-2 parts of the total amount of the auxiliary agent. The early strength agent is sodium sulfate or triethanolamine, accounting for 1-4 parts of the total amount of the auxiliary agent.
[0008] Among the above components, the penetrant is used to promote the penetration of the concrete sealing and curing agent into the concrete. Through the penetrant, the chemical components in the concrete react chemically to form a network structure in three-dimensional space, so that the components in the concrete are solidified into a solid entity, thereby obtaining a dust-free and dense whole, and permanently avoiding the precipitation of concrete dust from the surface gaps. Thereby effectively improving the strength, density and wear resistance of the concrete. Through the dispersing and stabilizing effect of the penetrant, the active ions contained in the water-based hardener, such as silicate ions, react with the unreacted free ions in the concrete, such as calcium ions, to form calcium silicate hydrates, so that the free ions in the concrete participate in the reaction, greatly improving the strength and hardness of the concrete. The defoamer is an organosilicon defoamer, accounting for 1-2 parts of the total amount of the additives, which can effectively eliminate the bubbles generated by the concrete curing agent during the production and use process, and improve the density and surface flatness of the concrete. The early strength agent is sodium sulfate or triethanolamine, accounting for 1-4 parts of the total amount of the additives, which can accelerate the early strength development of the concrete, so that the concrete can reach a certain strength in a shorter time and meet the requirements of engineering construction.
[0009] A method for preparing a concrete curing agent comprises the following steps: 1) Add lithium silicate, magnesium fluorosilicate and nano-silicon dioxide into water and stir at a stirring speed of 800 r / min for 45 minutes to fully mix them; 2) Add surfactant and continue stirring at the same stirring speed for 20 minutes to make the surfactant evenly dispersed in the solution; 3) Add additives as needed and stir evenly for 15 minutes to obtain the concrete curing agent.
[0010] A performance testing method for a concrete curing agent comprises the following steps: 1> Strength test: Step 1, prepare standard concrete specimens with a size of 150mm×150mm×150mm, divide the specimens into two groups, one group as a control group without any treatment, and the other group is evenly coated with the concrete curing agent of the present invention on the surface with a coating thickness of 0.8mm; Step 2: Place the two groups of specimens in a standard curing room at a temperature of 20°C ± 2°C and a relative humidity of more than 95% for 28 days; Step 3: Use a pressure testing machine to test the compressive strength of the specimen. Place the specimen on the pressure-bearing surface of the testing machine and apply pressure at a loading speed of 0.5MPa / s-1MPa / s until the specimen is destroyed; record the maximum pressure value at the time of destruction, and calculate the compressive strength based on the pressure-bearing area of the specimen; after testing, the compressive strength of the specimen treated with the concrete curing agent is 30%-40% higher than that of the control group; 2> Wear resistance test: Step 1, use a wear resistance test machine equipped with a 20kg grinding wheel and a counter; Step 2, fixing the treated concrete specimens and the control group specimens on the working table of the testing machine respectively; Step 3: Start the testing machine and make the grinding wheel rotate and rub on the surface of the specimen at a speed of 20r / min and a pressure of 100N; after 1000 revolutions of wear, turn off the testing machine, remove the specimen, and weigh the mass loss of the specimen with a balance; after testing, the mass loss of the specimen using the concrete curing agent is reduced by 40%-50% compared with the control group; 3> Impermeability test: Step 1, instrument preparation, use the impermeability tester, which consists of a pressure vessel, a pressure control system and a sealing device; Step 2: Place the treated specimens and the control specimens into the test mold of the impermeability tester and seal them with sealing materials; Step 3: Inject water into the pressure vessel and gradually increase the water pressure at a rate of 0.1 MPa per hour. Keep the pressure for 8 hours and observe the water seepage of the specimen. Record the water pressure value when water seepage starts, which is the anti-seepage performance index of the specimen. According to the test, the water seepage height of the specimen using the concrete curing agent is 60%-70% lower than that of the control group. 4> Durability test: Step 1, place the treated specimens and the control specimens in a test chamber simulating the natural environment, and set conditions such as dry-wet cycle (humidity cycle between 30% - 90%, temperature cycle between 10℃ - 50℃), freeze-thaw cycle (cycle between -20℃ and 20℃); Step 2: Observe the indicators. After 50 cycles, observe the changes in the appearance of the specimens, such as cracks and peeling. At the same time, use strength tests and other methods to detect the performance degradation of the specimens and evaluate the impact of the concrete curing agent on the durability of the specimens. After testing, the specimens using the concrete curing agent showed obvious advantages in durability, with no obvious changes in appearance and a strength degradation of less than 10%, while the control group specimens showed cracks, peeling, and other phenomena, and the strength degradation was greater than 30%.
[0011] Beneficial effects: 1. The concrete curing agent of the present invention adopts multiple active ingredients such as lithium silicate, magnesium fluorosilicate, nano silicon dioxide, etc., which can effectively improve the strength, hardness, wear resistance and durability of concrete.
[0012] 2. The addition of surfactants can improve the permeability of the curing agent, allowing it to better combine with concrete, thereby improving the curing effect.
[0013] 3. The use of additives can adjust the early strength development and meet the requirements of different engineering construction.
[0014] 4. The preparation method of the concrete curing agent of the present invention is simple, easy, low-cost and suitable for large-scale production.
[0015] 5. The curing agent has good environmental performance and does not pollute the environment. DETAILED DESCRIPTION
[0016] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0017] Embodiment 1 A concrete curing agent comprises the following components in parts by weight: 20 parts of lithium silicate, 12 parts of magnesium fluorosilicate, 8 parts of nano silicon dioxide, 3 parts of surfactant, additives (1.5 parts of defoamer, 1.5 parts of penetrant, 3 parts of early strength agent), and the balance is water.
[0018] Its preparation method: 1) Add lithium silicate, magnesium fluorosilicate and nano-silicon dioxide into water and stir for 45 minutes at a stirring speed of 800 r / min to fully mix them.
[0019] 2) Add the surfactant and continue stirring at the same stirring speed for 20 minutes to ensure that the surfactant is evenly dispersed in the solution.
[0020] 3) Add defoamer, penetrant and early strength agent, stir evenly for 15 minutes to obtain concrete curing agent.
[0021] Performance Test: ① Strength test: Prepare standard concrete specimens, one part of which is not treated as a control group, and the other part is treated according to the above application method. After 28 days of curing, the compressive strength of the specimens is tested using a pressure testing machine. The results show that the compressive strength of the specimens treated with concrete curing agent is 45MPa, and the compressive strength of the control group specimens is 35MPa, with a strength increase of 28.6%.
[0022] ② Wear resistance test: The treated concrete specimens and the control specimens were tested for wear resistance using a wear tester. After 1000 revolutions of wear, the mass loss of the specimen using the concrete curing agent was 1.2g, and the mass loss of the control specimen was 2.5g, a 52% reduction in mass loss.
[0023] ③ Impermeability test: The test specimens were tested for impermeability using an impermeability tester. After 8 hours, the water seepage of the specimens was observed. The water seepage height of the specimens using the concrete curing agent was 5mm, while the water seepage height of the control specimens was 15mm, and the water seepage height was reduced by 66.7%.
[0024] ④ Durability test: The treated specimens and the control group specimens were placed in a test chamber simulating the natural environment. After 50 dry-wet cycles and freeze-thaw cycles, there was no obvious change in the appearance of the specimens using the concrete curing agent, and the strength attenuation was 8%, while the control group specimens had slight cracks and the strength attenuation was 35%.
[0025] Embodiment 2 A concrete curing agent comprises the following components in parts by weight: 18 parts of lithium silicate, 11 parts of magnesium fluorosilicate, 7 parts of nano silicon dioxide, 2.5 parts of surfactant, additives (1 part of defoamer, 1 part of penetrant, 2 parts of early strength agent), and the balance is water.
[0026] Its preparation method: 1) Add lithium silicate, magnesium fluorosilicate and nano-silicon dioxide into water and stir for 45 minutes at a stirring speed of 800 r / min to fully mix them.
[0027] 2) Add the surfactant and continue stirring at the same stirring speed for 20 minutes to ensure that the surfactant is evenly dispersed in the solution.
[0028] 3) Add defoamer, penetrant and early strength agent, stir evenly for 15 minutes to obtain concrete curing agent.
[0029] Performance Test: ① Strength test: Prepare specimens with the same mix ratio as the factory floor concrete and conduct strength tests. The compressive strength of the treated specimens is 40MPa, while the compressive strength of the control group specimens is 32MPa, with a strength increase of 25%.
[0030] ② Wear resistance test: After 1000 revolutions of wear, the mass loss of the specimen using the concrete curing agent was 1.5g, and the mass loss of the specimen in the control group was 3g, and the mass loss was reduced by 50%.
[0031] ③ Anti-permeability test: After keeping the test pieces for 8 hours, the water seepage of the test pieces was observed. The water seepage height of the test pieces using the concrete curing agent was 6mm, while the water seepage height of the test pieces in the control group was 18mm, and the water seepage height was reduced by 66.7%.
[0032] ④ Durability test: The treated specimens and the control specimens were placed in a test chamber simulating the natural environment. After 50 dry-wet cycles and freeze-thaw cycles, the appearance of the specimens using the concrete curing agent remained basically unchanged, and the strength decayed by 7%, while the control specimens showed obvious cracks and peeling, and the strength decayed by 40%. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications of the above assumptions should also be regarded as the scope of protection of the present invention.
Claims
1. A concrete curing agent, characterized in that: The invention comprises the following components in parts by weight: 18-22 parts of lithium silicate, 10-13 parts of magnesium fluorosilicate, 7-10 parts of nano silicon dioxide, 2.5-3.5 parts of surfactant, 3-8 parts of auxiliary agent, and the balance is water.
2. A concrete curing agent according to claim 1, characterized in that: The surfactant is a nonionic surfactant.
3. A concrete curing agent according to claim 2, characterized in that: The nonionic surfactant is specifically fatty alcohol polyoxyethylene ether.
4. A concrete curing agent according to claim 1, characterized in that: The auxiliary agent is one or a combination of penetrant, defoamer or early strength agent.
5. A concrete curing agent according to claim 4, characterized in that: The penetrant is polyethylene oxide or an organic siloxane condensation polymer.
6. A concrete curing agent according to claim 4, characterized in that: The defoamer is an organosilicon defoamer, which accounts for 1-2 parts of the total amount of the auxiliary agent.
7. A concrete curing agent according to claim 4, characterized in that: The early strength agent is sodium sulfate or triethanolamine, accounting for 1-4 parts of the total amount of the auxiliary agent.
8. The method for preparing a concrete curing agent according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) Add lithium silicate, magnesium fluorosilicate and nano-silicon dioxide into water and stir at a stirring speed of 800 r / min for 45 minutes to fully mix them; 2) Add surfactant and continue stirring at the same stirring speed for 20 minutes to make the surfactant evenly dispersed in the solution; 3) Add additives as needed and stir evenly for 15 minutes to obtain concrete curing agent.
9. The performance testing method of a concrete curing agent according to any one of claims 1 to 7, characterized in that: The steps include: 1> Strength test: Step 1, prepare standard concrete specimens with a size of 150mm×150mm×150mm, divide the specimens into two groups, one group as a control group without any treatment, and the other group is evenly coated with the concrete curing agent of the present invention on the surface with a coating thickness of 0.8mm; Step 2: Place the two groups of specimens in a standard curing room at a temperature of 20°C ± 2°C and a relative humidity of more than 95% for 28 days; Step 3: Use a pressure testing machine to test the compressive strength of the specimen; place the specimen on the pressure-bearing surface of the testing machine, and apply pressure at a loading speed of 0.5MPa / s-1MPa / s until the specimen is destroyed; record the maximum pressure value at the time of destruction, and calculate the compressive strength based on the pressure-bearing area of the specimen; 2> Wear resistance test: Step 1, use a wear resistance tester equipped with a 20kg grinding wheel and a counter; Step 2, fixing the treated concrete specimens and the control group specimens on the working table of the testing machine respectively; Step 3: Start the testing machine and make the grinding wheel rotate and rub on the surface of the specimen at a speed of 20r / min and a pressure of 100N; after 1000 revolutions of wear, turn off the testing machine, remove the specimen, and weigh the mass loss of the specimen with a balance; 3> Impermeability test: Step 1, instrument preparation, use the impermeability tester, which consists of a pressure vessel, a pressure control system and a sealing device; Step 2: Place the treated specimens and the control specimens into the test mold of the impermeability tester and seal them with sealing materials; Step 3: inject water into the pressure vessel and gradually increase the water pressure at a rate of 0.1 MPa per hour. After maintaining the pressure for 8 hours, observe the water seepage of the test piece. Record the water pressure value when water seepage begins, which is the anti-seepage performance index of the test piece. 4> Durability test: Step 1, place the treated specimens and the control specimens in a test chamber simulating the natural environment, and set conditions such as dry-wet cycle (humidity cycle between 30% - 90%, temperature cycle between 10℃ - 50℃), freeze-thaw cycle (cycle between -20℃ and 20℃); Step 2: Observe the indicators. After 50 cycles, observe the changes in the appearance of the specimens, such as cracks and peeling. At the same time, use strength testing and other methods to detect the performance degradation of the specimens and evaluate the impact of the concrete curing agent on the durability of the specimens.
